2002
DOI: 10.1046/j.1532-5415.2002.50513.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Older Adults Expect to Age Successfully? The Association Between Expectations Regarding Aging and Beliefs Regarding Healthcare Seeking Among Older Adults

Abstract: OBJECTIVES:To measure expectations regarding aging among community-residing-older adults, identify characteristics associated with having low expectations regarding aging, and examine whether expectations regarding aging are associated with healthcare-seeking beliefs for age-associated conditions. DESIGN: Self-administered mail survey. SETTING: Greater Los Angeles. PARTICIPANTS: Four hundred twenty-nine of 588 (73%) randomly selected community-residing adults aged 65 to 100 (mean age 76) cared for by 20 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
189
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(218 citation statements)
references
References 28 publications
22
189
0
7
Order By: Relevance
“…Yet, positive expectations have also been found in older people (Connidis 1989;Timmer et al 2002) and such a positive frame of mind was found to be related to subjective wellbeing ) and longevity (Levy et al 2002). By contrast, a negative frame of mind was found to be related to admission to a nursing home (Haken et al 2002;Steverink 2001), to problems in adapting to widowhood (Nieboer et al 1999) and to attaching low importance to seeking help for age-associated conditions, such as depression, memory impairment and urinary incontinence (Sarkisian et al 2002).…”
Section: Self-efficacy Beliefsmentioning
confidence: 97%
“…Yet, positive expectations have also been found in older people (Connidis 1989;Timmer et al 2002) and such a positive frame of mind was found to be related to subjective wellbeing ) and longevity (Levy et al 2002). By contrast, a negative frame of mind was found to be related to admission to a nursing home (Haken et al 2002;Steverink 2001), to problems in adapting to widowhood (Nieboer et al 1999) and to attaching low importance to seeking help for age-associated conditions, such as depression, memory impairment and urinary incontinence (Sarkisian et al 2002).…”
Section: Self-efficacy Beliefsmentioning
confidence: 97%
“…21,22 GPs and patients perceive it an accepted part of ageing to become depressed. 23 Late-life depression is viewed as 'justifiable' and understandable. 9 Low expectations of treatment and therapeutic nihilism have been documented.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Seniority of human kind is a complicated and complex process which is replete with considerable issues which have always been brought to the light by different realms including psychology, medical and social realms (Sarkisian et al, 2002). Throughout the history, this period has always been considered as a failing period during which most of the psychosomatic functions are on the wane (Cheverie, 2008).…”
Section: Introductionmentioning
confidence: 99%